Generic structure of introductions in entrepreneurship research articles / Fatemeh Naderi Osat - Fatemeh Naderi, Osat (2012)
The purpose of the present study is twofold. Firstly it seeks to find the generic structures that are inherent in the introduction sections of entrepreneurship research articles and secondly it investigates the role of experiential metafunction and its distribution in realization of obligatory generic elements that are found in the data. The approach applied is a combination of Halliday and Hasan’s (1989) model of genre analysis to find the generic structure potential (GSP) of the introduction sections as well as Halliday’s (1994) model of transitivity analysis to find the typicality of the process types and their contribution in the realization of the obligatory elements. The corpus comprises 20 research article introduction sections that are published from 2010 onward in the Journal of Small Business and Entrepreneurship and Small Business and Enterprise Development. The analysis reveals that 13 types of generic elements might occur in the entrepreneurship research articles introductions. Two of these elements such as ‘Purpose of study’ and ‘Previous study’ element are present in the whole data while others are found to be optional. Based on the obligatory, optional and recursive elements found on the data, the model of Generic Structure Potential (GSP) of the entrepreneurship research article’s introduction sections is proposed. Moreover, in the second phase of analysis the findings reveal that the typicality of the process types within each obligatory element is mostly in line with the function that each obligatory generic element fulfills in that particular genre. As an instance, in the present study, the ‘purpose of study’ element is mostly recognized with Mental processes and Relational processes while the ‘Previous study’ element is highly characterized with Material and Mental processes.